Clinical investigation to modulate the effect of fenugreek polysaccharides on type-2 diabetes. (July 2019) - Rashid, Raheela; Ahmad, Hajra; Ahmed, Zaheer; Rashid, Farhat; Khalid, Nauman
Abstract: Fenugreek is used extensively as spice, herb, food and medicine. Its active ingredient includes galactomannan, saponins, trigonelle, diosgenin and 4-hydroxyisoleucine has pronounced effect in controlling diabetes. The effect of galactomannan derived from fenugreek on fasting blood glucose, HbA1c and lipid profile was observed in newly diagnosed type-2 diabetics. The study was conducted as a 12-week interventional randomized, single blind control study with 4-week washout period on newly diagnosed type-2 diabetics (n = 64). After systematic randomization study, the group (n = 32) received 1 gm/day galactomannan and a control group (n = 32) received placebo. Fasting blood glucose, HbA1c and lipid profile were measured thrice i.e. at baseline, 12-weeks and finally after washout period of 4-weeks. Mean and SD were calculated for each variable. The study group showed significant decrease in fasting blood glucose, HbA1c, total cholesterol, triglyceride and low-density lipoprotein. Although, there was improvement in high density lipoprotein but was not significantly raised. The results suggest that galactomannan in low dose can be used as alternative therapy for management of hyperglycemia and dyslipidemia in newly diagnosed type-2 diabetics.